Structural and mechanistic insights into ribosomal ITS2 RNA processing by nuclease-kinase machinery - Jiyun Chen; Hong Chen; Shanshan Li; Xiaofeng Lin; Rong Hu; Kaiming Zhang; Liang Liu (eLife, 2024)
Precursor ribosomal RNA (pre-rRNA) processing is a key step in ribosome biosynthesis and involves numerous RNases. A HEPN (higher eukaryote and prokaryote nucleotide binding) nuclease Las1 and a polynucleotide kinase Grc3 assemble into a tetramerase responsible for rRNA maturation. Here, we report the structures of full-length Saccharomyces cerevisiae and Cyberlindnera jadinii Las1-Grc3 complexes, and C. jadinii Las1. The Las1-Grc3 structures show that the central coiled-coil domain of Las1 facilitates pre-rRNA binding and cleavage, while the Grc3 C-terminal loop motif directly binds to the HEPN active center of Las1 and regulates pre-rRNA cleavage. Structural comparison between Las1 and Las1-Grc3 complex exhibits that Grc3 binding induces conformational rearrangements of catalytic residues associated with HEPN nuclease activation. Biochemical assays identify that Las1 processes pre-rRNA at the two specific sites (C2 and C2′), which greatly facilitates rRNA maturation. Our structures and specific pre-rRNA cleavage findings provide crucial insights into the mechanism and pathway of pre-rRNA processing in ribosome biosynthesis.